Low circulatory Fe and Se levels with a higher IL-6/IL-10 ratio provide nutritional immunity in tuberculosis - Kaushik, Sandeep R.; Sahu, Sukanya; Guha, Hritusree; Saha, Sourav; Das, Ranjit; Kupa, Rukuwe-u; Kapfo, Wetetsho; Deka, Trinayan; Basumatary, Rumi; Thong, Asunu; Dasgupta, Arunabha; Goswami, Bidhan; et al. (Frontiers in immunology, 2023)
Tuberculosis (TB) patients show dysregulated immunity, iron metabolism, and anemia. In this study, circulatory cytokines, trace metals, and iron-related proteins (hepcidin, ferroportin, transferrin, Dmt1, Nramp1, ferritin, ceruloplasmin, hemojuvelin, aconitase, and transferrin receptor) were monitored in case (active tuberculosis patients: ATB) and control (non-tuberculosis: NTB and healthy) study populations ( n = 72, male: 100%, mean age, 42.94 years; range, 17–83 years). Using serum elemental and cytokine levels, a partial least square discriminate analysis model (PLS-DA) was built, which clustered ATB patients away from NTB and healthy controls. Based on the PLS-DA variable importance in projection (VIP) score and analysis of variance (ANOVA), 13 variables were selected as important biosignatures [IL-18, IL-10, IL-13, IFN-γ, TNF-α, IL-5, IL-12 (p70), IL-1β, copper, zinc, selenium, iron, and aluminum]. Interestingly, low iron and selenium levels and high copper and aluminum levels were observed in ATB subjects. Low circulatory levels of transferrin, ferroportin, and hemojuvelin with higher ferritin and ceruloplasmin levels observed in ATB subjects demonstrate an altered iron metabolism, which partially resolved upon 6 months of anti-TB therapy. The identified biosignature in TB patients demonstrated perturbed iron homeostasis with anemia of inflammation, which could be useful targets for the development of host-directed adjunct therapeutics.